Coffee as a Livelihood Support for Small Farmers: A Case Study of Hamsapur Village in Nepal - Kana Aoki; Murari Suvedi (Journal of International Agricultural and Extension Education, 2012)
Coffee production as an income-generating project has been promotedby the Nepalese governmentwith the collaboration of international development agencies. Those areas of Nepal withsuitable climate and geography have the potential to grow high-quality Arabica coffee fortheinternational market. This research examines the possibilities of organiccoffee production as a livelihood support for small-scale farmers in Hamsapur village in Nepal. Using value chain analysis, coffee producers and collectors were interviewed,and semi-structured interviews were conducted with key informants. Findings showed that local farmers have great interest in coffee production;however, the income generation promises have not been realizedbecause of insufficient quality,alack oftransparency in the local coffee market,andorganizational issues. Analysis showedthere is a need for alternativebusinessrelationshipswith producersalong the coffee value chain that result in greater benefit to farmers.
Keywords: Value Chain Study; Coffee; Nepal; Small-Scale Farmers; Social Business; Rural Development